Avaliação de padrões de design de interação em aplicativos móveis para usuários idosos - Silva, Leonardo Filipe da (2020)
Governments of different spheres have mobilized to implement e-government services for their citizens. This effort is made to offer less bureaucratic and faster access to government services and information. However, such a comprehensive strategy can become problematic and potentially marginalizing to citizens with limited access or skills. Older people, in particular, are in increasing numbers and have specific needs due to the decline in their physical and cognitive abilities resulting from ageing. Concomitantly, the ubiquity of mobile applications requires frequent improvement of the interface design process for users, in which the use of interaction design patterns can facilitate documentation and the reuse of proven and recurring solutions in the process of building these interfaces, that can also contribute to e-government applications. Analyzing the usability aspects of mobile interaction design patterns in the context of e-government systems can contribute to optimizing processes and developing successful projects for users. Considering there are limitations in the mobile context, the increase in the ageing population, and the lack of knowledge about the adequacy of interaction design patterns in government applications for older users, investigating those issues is very relevant. This study aimed to develop a set of recommendations for the use of interaction design patterns in mobile e-government applications with a focus on older users. The study included the following methodological steps: 1) mapping of interaction design patterns for mobile applications based on the analysis of 1162 studies in the literature; 2) application of a survey of 66 older and older adults, listing questions about their use and perception of the internet and government services; 3) analysis of Brazilian government applications to identify interaction design patterns that were implemented; 4) usability tests of a sample with five e-government applications with elderly users to identify problems in their interfaces; 5) analysis of usability problems about interaction design patterns; and finally 6) construction of recommendations on interaction design patterns that assist in the development of the interfaces of electronic government applications for elderly users. As a result, the survey obtained information about the use and perception of older citizens about the domain of electronic government and the internet, including the ubiquity of mobile devices and the internet, low level of ICT literacy among the elderly, and high rate of use of government services in general. The systematic mapping study yielded 336 mobile interaction design patterns collected from 23 studies. The usability tests of Brazilian government applications resulted in a total of 134 usability problems, 74 of which are related to patterns. Finally, 44 usability recommendations were established, related to 15 interaction design patterns. The contributions of this study aim to improve the implementation of mobile interaction design patterns, mitigating usability barriers in government applications, and promoting a better experience for older users.